In-line coagulation prior to UF of treated domestic wastewater - foulants removal, fouling control and phosphorus removal - Zheng, X.; Plume, S.; Ernst, M.; Croue, Jean-Philippe; Jekel, M. (Elsevier BV, 2012)
The present work investigated fouling control and phosphorus removal by applying in-line coagulation prior to ultrafiltration (UF) of treated domestic wastewater. Experiments were conducted in both lab- and pilot-scale under close to neutral pH condition. Lab-scale foulant removal tests showed that increasing the dosage of FeCl3, AlCl3 and polymeric aluminum chloride (PACl) can improve biopolymer removal. Specifically, PACl reduced preferentially the proteinaceous fraction of biopolymer while the other two coagulants showed no significant preference. The filterability of water samples was improved after coagulation, which is contributed to biopolymer removal and the formation of larger particles. Pilot UF experiments demonstrated that in-line coagulation improved the performance of UF to a large extent. Within 0.037-0.148mmol Me3+/L dosage range, adding more FeCl3 and AlCl3 slowed down the development of trans-membrane pressure (TMP) correspondingly, while changing PACl dosage showed little effect on the variation of TMP increase rate. Further investigations indicated that PACl related precipitates contributed to more irreversible fouling than that which the monomeric coagulants made. Fouling control is thus considered as a co-effect determined by foulant removal efficiency, fouling layer structure and the adherence of hydrolysis products/precipitates onto the membrane. With respect to phosphorus removal, dosing FeCl3 and AlCl3 achieved higher removal efficiency than using PACl. Based on lab- and pilot-scale results, dosing FeCl3 and AlCl3 at a relative dosage of over 2.5mol Me3+ per mol total phosphorus (TP) in feedwater is necessarily required to keep the TP concentration under 50µg/L in UF permeate.